Optimization of mannanase expression in Aspergillus niger for enhanced production of mannan oligosaccharides - Zhang, Hui; Tang, Huakai; Ma, Tingting; Ma, Xiaofei; Kou, Yuwei; Wang, Bing; He, Jiahuan; Li, Jie (Frontiers in Bioengineering and Biotechnology, 2026)
Mannan oligosaccharides (MOS) are high-value prebiotics widely applied in the food, feed, and pharmaceutical industries. Mannanase, as the key rate-limiting enzyme in the biosynthesis of MOS, directly determines MOS yield and production cost based on its expression level. However, current industrial enzyme sources commonly exhibit low expression levels, poor secretion efficiency, and inadequate stability, severely limiting the reliable production of high-performance enzyme preparations. To overcome this core bottleneck, this study employed Aspergillus niger-an established industrial host-as the chassis organism and systematically improved the expression level and extracellular secretion efficiency of mannanase through integrated multi-dimensional strategies, including gene copy number regulation, secretion pathway optimization, and signal peptide modification. This project aims to provide efficient enzyme resources and robust technical support for the cost-effective and scalable biosynthesis of MOS. Specifically, Doubling the gene copy number enhanced man transcript levels 92.00% and extracellular mannanase activity by 66.25%, while tripling the copy number induced the unfolded protein response (UPR) and impaired growth. Deletion of AsAA relieved secretion stress, leading to a 10.11% increase in transcription and a 175.64% improvement in enzyme activity. Similarly, deleting Vps10 resulted in a 24.48% increase in transcription and a 30.08% increase in enzyme activity, likely by reducing degradation of folded protein. Replacement of the SglaA signal peptide with SpepB resulted in a 7.29% increase in transcript abundance and a 15.41% increase in enzyme activity. RT-qPCR analysis confirmed upregulation of several UPR-related genes (hacA, bipA, and pdiA) in most strains, consistent with ER stress under high expression burdens. The recombinant mannanase demonstrated high hydrolytic activity against konjac powder, yielding a total MOS content of 94.47% in the hydrolysis products, which highlights its significant potential for the efficient production of functional oligosaccharides. This study not only provides essential technical support for the industrial-scale synthesis of MOS, but also establishes a scalable engineering framework for the efficient heterologous expression of industrial enzymes.